2000
DOI: 10.1017/s0952836900003010
|View full text |Cite
|
Sign up to set email alerts
|

Hyperextended call note repertoire of the endemic Madagascar treefrog Boophis madagascariensis (Rhacophoridae)

Abstract: Vocalizations of Boophis madagascariensis (Rhacophoridae) males were recorded in a mid-elevation rain forest in eastern Madagascar. Call notes made by males of this species were classi®ed into 28 types. This represents the largest known call repertoire of any amphibian. The calls range widely in spectral characteristics from a narrowband, nearly pure-tone to broadband`rip' notes, to even broader band, pulsatile`iambic' notes consisting of up to 23 pulses. Even considering all`iambic' notes as variants of one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Anuran call variation and call repertoire have only rarely been described for single species (e.g. Narins et al 2000;Toledo & Haddad 2005), and the role and function of mate choice, mate competition and their consequences for speciation are not well understood. However, recent studies on within-species call variation suggest that acoustic traits seem to be subject to more rapid evolution than are other traits (for a review see Gerhardt & Huber 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Anuran call variation and call repertoire have only rarely been described for single species (e.g. Narins et al 2000;Toledo & Haddad 2005), and the role and function of mate choice, mate competition and their consequences for speciation are not well understood. However, recent studies on within-species call variation suggest that acoustic traits seem to be subject to more rapid evolution than are other traits (for a review see Gerhardt & Huber 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Kroodsma, 1985;Podos et al, 1992;reviewed in Catchpole & Slater, 2003), and acoustic sequences in other taxa (e.g. Narins et al, 2000;Larson, 2004). Humans are usually considered to be good at visual pattern recognition -and better than most computer algorithms (Ripley, 2007;Duda, Hart & Stork, 2012), which makes visual classification an attractive approach to identifying acoustic units.…”
Section: (4) Identifying Analytical Unitsmentioning
confidence: 99%
“…Model validation techniques include the sequential and X 2 tests (Anderson & Goodman, 1957). For instance, Narins et al (2000) used a permutation test (Adams & Anthony, 1996) to evaluate the hypothesis that a frog with an exceptionally large vocal repertoire, Bufo madagascariensis, emitted any = P e (B-X ) = 0.5, and when in state Y , acoustic unit A is much more likely P e (A-Y ) = 0.9 than B P e (B-Y ) = 0.1. Transitioning from state X to state Y occurs with probability P t (X → Y ) = 0.6, whereas from state Y to state X with probability P t (Y → X ) = 0.3.…”
Section: Analysis Of Sequencesmentioning
confidence: 99%
“…Other studies have also shown complex calls of anurans (e.g. Narins et al, 2000;Feng et al, 2002;Brandão & Heyer, 2005;Toledo & Haddad, 2005). The intraspecific and/or individual variations are mainly in dominant frequency and duration of each note, number and sequence order of pulses or notes, but a high call diversity as observed in L. natalensis is not common.…”
Section: Discussionmentioning
confidence: 91%